2015
DOI: 10.1016/j.jtcvs.2014.11.075
|View full text |Cite
|
Sign up to set email alerts
|

Long-term fate of the aortic valve after an arterial switch operation

Abstract: Reoperation on the aortic valve is rarely necessary, even late after an ASO, but a significant number of patients do have late aortic regurgitation and continue to need observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 19 publications
7
22
1
2
Order By: Relevance
“…It means that LSRs after ASO are rare (overall incidence of 1.4%) and are required mainly for neoaortic valve insufficiency (0.68%)(similar to other single-center reports in which the frequency ranged from 0.6%-1.3%) [14,15,26] and for coronary artery malperfusion/ischemia (0.26%) (which was lower than in other single-center reports in which it was up to 2% [5,24]. Patients with CAP were treated by means of coronary revascularization or more conservatively by relocating the coronary artery ostium, when indicated, to treat late kinking or distortion of the proximal coronary course.…”
Section: Commentsupporting
confidence: 82%
See 1 more Smart Citation
“…It means that LSRs after ASO are rare (overall incidence of 1.4%) and are required mainly for neoaortic valve insufficiency (0.68%)(similar to other single-center reports in which the frequency ranged from 0.6%-1.3%) [14,15,26] and for coronary artery malperfusion/ischemia (0.26%) (which was lower than in other single-center reports in which it was up to 2% [5,24]. Patients with CAP were treated by means of coronary revascularization or more conservatively by relocating the coronary artery ostium, when indicated, to treat late kinking or distortion of the proximal coronary course.…”
Section: Commentsupporting
confidence: 82%
“…It is now clear that a certain percentage of patients will need further reintervention/ reoperation [10,15,[17][18][19], which in the majority of patients is on the right side of the heart, for neopulmonary stenosis either at the anastomosis site or at the pulmonary artery bifurcation (after the LeCompte maneuver) [7,9,10]. Less commonly, reoperations involve the left side of the heart, such as the neoaortic valve, the aortic root, the subaortic area, and the coronary arteries [4,5,9].…”
Section: Commentmentioning
confidence: 99%
“…We have previously reported an operative mortality of 2.8% in 618 children with TGA, who underwent ASO from 1983 to 2009 at the Royal Children's Hospital, with an operative mortality higher for those with a ventricular septal defect (VSD) compared to those with an intact interventricular septum (IVS) (3.8% versus 1.8%) [6]. Long-term survival for our patients was 96% at 20 years postoperatively, similar to that reported by others [8,12]. While not often the focus of ASO studies, postoperative morbidity has been shown to be significantly higher in more complex anatomy requiring the ASO with respect to longer duration of ventilation and postexubation hospital stay [13].…”
Section: Current Outcomes Of the Asosupporting
confidence: 86%
“…MORTALITY. Early mortality after the ASO in the modern era is reported between 1% and 3% [6][7][8]. Mortality is higher in more complex forms of transposition including Taussig-Bing anomaly (TBA) and TGA with aortic arch obstruction (AAO), such as coarctation of aorta (COA) or interrupted aortic arch (IAA) [9][10][11].…”
Section: Current Outcomes Of the Asomentioning
confidence: 99%
“…However, patients with an arterial switch thus far have done well, with neoaortic dilation, aortic valve regurgitation, supravalvular and branch pulmonary stenosis, and coronary abnormalities developing in a minority of patients. [211][212][213] Women with an arterial switch repair are anticipated to do well in pregnancy, provided that there are no hemodynamically important residua such as valve dysfunction, supravalvular or branch pulmonary stenosis, supravalvular AS, coronary ischemia, or ventricular dysfunction. Thus far, there are scant data on pregnancy in women with an arterial switch repair, and complications in 1 series were related to associated abnormalities that would have been identified as high risk in any circumstance (mechanical valve replacement and left ventricular dysfunction).…”
Section: Arterial Switchmentioning
confidence: 99%